Exploration of Cosmetic Factors Contributing to Rhinoplasty among Both Genders in Iraqi Kurdistan - Amin Kamali, Aram Salih Mohammed; Hassan Rostam, Hedi; Khdir, Awat Alla; Aula Mina, Omer (Kurdistan Journal of Applied Research, 2020)
The most outstanding feature of face is the nose which is in furthering than any other feature to facial characteristics. Furthermore, the appealing aspects of the nose is an essential olfactory organ. Over and beyond the aesthetic and functional aspects the client’s reaction to his/her own nose as well as the reaction of the people around to it impacts to the psychic characteristics. A non-probability purposive sample of this cross - sectional descriptive study was consisted of 100 young male and female in Kurdish ethnicity, their ages ranged between 21-25 years. The main objective of the study is conducted to assess the cosmetic factors, contribute to Rhinoplasty among both genders at Raparin District. The data collecting period were during the (December 15th, 2019 to January 5th, 2020). A self-administration questionnaire was used for data collection and it was designed according guidelines, literatures, and articles concerning Rhinoplasty; which consisted of 26 variables. Data were analyzed using SPSS Version 23. The study results revealed that most of participants (67%) were female when only (17%) of them were married, however, more than half (67%) were students. Whenever, they about (56%) were barely sufficient in their monthly income. Moreover, about (61%) of participants interested to surgically alter the appearance of their nose, closely two-third (74%) of participants wanted to surgically change the function of their nose. Therefore, almost (87%) of participant relatives have been operated with Rhinoplasty. Also, the study demonstrated there is a statistically significant relationship between cosmetic factors contributing to Rhinoplasty with age (p=0.035) and occupation (p=0.037). When, there were strongly statistically significant association between cosmetic un-functional factors contributing to Rhinoplasty with level of education (p=0.003). The study recommended to plastic surgeons evaluate patients carefully before Rhinoplasty surgery to get rid of unnecessary surgeries because there are lots of complications related to Rhinoplasty and the psychological needs of the patients who undergo Rhinoplasty should be considered.